TRPV4 is a regulator in P. gingivalis lipopolysaccharide‐induced exacerbation of macrophage foam cell formation. Issue 7 (13th April 2019) - Gupta, Nabyendu; Goswami, Rishov; Alharbi, Mazen O.; Biswas, Debabrata; Rahaman, Shaik O.
Abstract: Porphyromonas gingivalis (P.g), a major causative agent of periodontitis, has been linked to atherosclerosis, a chronic inflammatory vascular disease. Recent studies have suggested a link between periodontitis and arterial stiffness, a risk factor for atherosclerosis. However, the mechanisms by which P.g infection contributes to atherogenesis remain elusive. The formation of lipid‐laden macrophage "foam cells" is critically important to development and progression of atherosclerosis. We have obtained evidence that TRPV4 (transient receptor potential channel of the vanilloid subfamily 4), a mechanosensitive channel, is a regulator of macrophage foam cell formation both in response to P.g‐derived lipopolysaccharide (PgLPS) or to an increase in matrix stiffness. Importantly, we found that TRPV4 activity (Ca 2+ influx) was increased in response to PgLPS. Genetic deletion or chemical antagonism of TRPV4 channels blocked PgLPS‐triggered exacerbation of oxidized LDL (oxLDL)‐mediated foam cell formation. Mechanistically, we found that (1) TRPV4 regulated oxLDL uptake but not its cell surface binding in macrophages; (2) reduced foam cell formation in TRPV4 null cells was independent of expression of CD36, a predominant receptor for oxLDL, and (3) co‐localization of TRPV4 and CD36 on the macrophage plasma membrane was sensitive to the increased level of matrix stiffness occurring in the presence of PgLPS. Altogether, our results suggest that TRPV4 channels play an essential role in P.g‐induced exacerbation of macrophage foam cell generation through a mechanism that modulates uptake of oxLDL. Abstract : We have obtained evidence that TRPV4 (transient receptor potential channel of the vanilloid subfamily 4), a mechanosensitive channel, is a regulator of macrophage foam cell formation in response to P.g‐derived lipopolysaccharide (PgLPS). Our results suggest that TRPV4 channels play an essential role in P.g‐induced exacerbation of macrophage foam cell generation through a mechanism that modulates uptake of oxLDL.